The Effectiveness of Self-Regulation Counseling Approach to Reduce Ego Depletion in College Students - Setiawan, Bambang; Suteja , Jaja; Novianti, Herny; Fikri, Abdul (COUNS-EDU: The International Journal of Counseling and Education, 2026)
The transition to higher education increases the demands of self-regulation of students, which has the potential to cause ego depletion. This research aims to test the effectiveness of the Self-Regulation Counseling Approach (SRCA) in reducing the ego depletion of students. The research uses a quasi-experimental design with a pretest-posttest control group pattern. The participants in this study consisted of 729 people who were selected through systematic random sampling and divided into an experimental group of 15 people and a control group of 15 people The population of this study comprised 729 individuals. A total of 30 participants were selected through systematic random sampling and subsequently assigned to an experimental group (n = 15) and a control group (n = 15). The measurement of ego depletion uses a questionnaire developed by the researcher with 58 items, which has met the content validity (CVI = 0.80), construct validity through the Pearson Product Moment correlation test, and high reliability (Cronbach's Alpha = 0,955). Data analysis uses ANCOVA to control for differences in the initial score. The results of the study showed that there was a significant difference between the experimental group and the control group on the post-test score after controlling for the pre-test (p < 0.05), where the experimental group showed a greater decrease in ego depletion. This finding indicates that SRCA has the potential to contribute to reducing student ego depletion, although further research with a stricter design is still needed.